A Comparative Study on the Development Strategies of Renewable Energy Industries in China and the United States Based on an Innovation Perspective - Xu, Yifei (Transactions on Economics, Business and Management Research, 2024)
This paper conducts a comparative study on the development strategies of renewable energy industries in China and the United States, highlighting the challenges in transitioning to renewable energy and underscoring the importance of political will. It aims to elucidate the differences in approaches between the two countries to inform future policy innovations. In China, the focus lies on fostering innovation in green energy technologies, with significant investments in research and development, disruptive technologies, and ambitious renewable energy capacity targets. Conversely, the United States is transitioning towards decarbonization through regulatory measures, financial incentives, and innovative financing mechanisms to accelerate the adoption and deployment of existing renewable energy technologies. While both countries are expanding their renewable energy sectors, China emphasizes innovation and government-led initiatives, whereas the USA relies more on market mechanisms, state roles, and private capital. These differences reflect the unique economic, political, and technological contexts of each nation, shaping their respective approaches to renewable energy development. Moving forward, policymakers can draw insights from these comparative analyses to enhance their renewable energy strategies. By leveraging the strengths of each approach and addressing challenges collaboratively, both countries can advance towards a more sustainable energy future.